2019
DOI: 10.1002/mgg3.736
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant mitochondrial membrane protein‐associated neurodegeneration (MPAN)

Abstract: Background Mitochondrial membrane protein‐associated neurodegeneration (MPAN) is caused by pathogenic sequence variants in C19orf12 . Autosomal recessive inheritance has been demonstrated. We present evidence of autosomal dominant MPAN and propose a mechanism to explain these cases. Methods Two large families with apparently dominant MPAN were investigated; additional singleton cases of MPAN were identified. Gene sequencing and multiplex ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 11 publications
4
61
0
1
Order By: Relevance
“…Second, a previous report suggested that the C19orf12 variant has dominant effect, similar to our observations. But this report is not yet listed in OMIM 28 . Next, to test if the genetic properties of recessive variants are different from those of dominant variants, several parameters were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Second, a previous report suggested that the C19orf12 variant has dominant effect, similar to our observations. But this report is not yet listed in OMIM 28 . Next, to test if the genetic properties of recessive variants are different from those of dominant variants, several parameters were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, about 50 C19ORF12 variants have been found to relate to the MPAN phenotype, including missense/nonsense, indels and splicing mutations (HGMD ® Professional 2020.1; accessed 7 October 2020). Although MPAN is considered an AR condition, a single C19ORF12 mutation can lead to the same clinical phenotype as biallelic variants [ 129 ]. The mutations with AR inheritance are degraded by the NMD (nonsense-mediated decay) system, generating haploinsufficiency.…”
Section: Nbia Types Related To Lipid Metabolism and Membrane Remodmentioning
confidence: 99%
“…In contrast, the mutations with autosomal dominant (AD) inheritance may be located in the final part of C19ORF12 mRNA and may escape from NMD. Therefore, the resulting protein would have a dominant negative effect on the WT that may explain the duality in MPAN inheritance [ 129 ]. Interestingly, alternative clinical phenotypes to MPAN have been reported for distinct C19ORF12 variants: the c.187G>C (p.A63P) mutation causes an AR form of spastic paraplegia with amyotrophy (SPG43) [ 130 , 131 ], the c.197-199del3 variant leads to MPAN phenotype aggravated with traits of juvenile amyotrophic lateral sclerosis (ALS) [ 132 ], and a clinical picture of Karak pallido-pyramidal syndrome has been described for the c.157G>A (p.G53R) mutation [ 133 ].…”
Section: Nbia Types Related To Lipid Metabolism and Membrane Remodmentioning
confidence: 99%
“…Although the study on the first family with MPAN reports it as an autosomal recessive condition, 3 dominant inheritance of the disease was confirmed recently. 4 Independent of the inheritance pattern, most MPAN cases are phenotypically similar at both clinical and neuropathologic levels. 4 …”
mentioning
confidence: 99%
“… 4 Independent of the inheritance pattern, most MPAN cases are phenotypically similar at both clinical and neuropathologic levels. 4 …”
mentioning
confidence: 99%